Pemanfaatan Potensi Sampah Sebagai Sumber Energi - Ana Afifatur Rakhmah; Diky Ramadhan; Reiki Fatah Zahrasiwi; Wahyu Kurniawati (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
The problem of waste management is one of the main challenges in the modern era which harms the environment. Innovative and sustainable solutions need to be developed to overcome this waste problem. One promising approach is using waste as a source of electrical energy. In this abstract, we explain the concept of using waste as a source of electrical energy, including the methods used and their benefits. We also convey the urgency of using waste as a source of electrical energy to reduce the negative impact of waste on the environment and to meet sustainable energy needs. Apart from that, this article also highlights the importance of government support, the role of the community, and the development of more efficient technology in realizing the successful use of waste as a source of electrical energy.